Sentido y alcance del Tratado V (V 9) de Plotino: ¿un manual (ἐγχειρίδιον) de doctrina (neo-)platónica? - Martin de Blassi, Fernando G. (Pontificia Universidad Católica del Perú, 2025)
“Meaning and scope of Treaty V (V 9) of Plotinus: a manual (ἐγχειρίδιον) of (neo-)platonic doctrine?”. If it is true that Plotinus’ thought has been characterized by specialists as “the swan song of Greek philosophy” (López Eire 1973: 77) or the “glory of ancient philosophy” (Moreau 1970), this is largely due to the exegetical synthesis that the philosopher knew how to undertake with respect to the Platonic and Peripatetic doctrines, inherited from the Hellenic tradition. Now, Treaty V (V 9) of the enneadic set, according to the chronological order drawn up by Porphyry, seems to anticipate the display of erudition that the Neoplatonist master would later develop in other long-term works, belonging more pertinently to the teaching phase of Plotinus, which Porphyry places it in the middle and mature period. Thus, the present study aims to elucidate through a descriptive and critical analysis the philosophical frameworks that are thematized in the Treaty chosen for this occasion.

Si es cierto que el pensamiento de Plotino ha sido caracterizado por los especialistas como “el canto del cisne de la filosofía griega” (López Eire 1973: 77) o bien como la “gloria de la filosofía antigua” (Moreau 1970), ello se debe en gran medida a la síntesis exegética que el filósofo supo acometer con respecto a las doctrinas platónicas y peripatéticas, heredadas de la tradición helénica. Ahora bien, el Tratado V (V 9) del conjunto eneádico, según el orden cronológico trazado por Porfirio, parece anticipar el alarde de erudición que el maestro neoplatónico desarrollará con posterioridad en otros trabajos de largo aliento, pertenecientes con mayor pertinencia a la fase docente de Plotino, que Porfirio ubica en el período medio y de madurez. Así las cosas, el presente estudio pretende dilucidar mediante un análisis descriptivo y crítico los encuadres filosóficos que son tematizados en el Tratado escogido para esta ocasión.
Meaning and scope of Treaty V (V 9) of Plotinus: a manual (ἐγχειρίδιον) of (neo-)platonic doctrine?
Keywords: Ideas; Intelligence; Plotinus; Being; Treaty V; Ideas; Inteligencia; Plotino; Ser; Tratado V; https://purl.org/pe-repo/ocde/ford#6.03.01